Diagnosis and Treatment of Multibacillary Leprosy Borderline Lepromatous Type: A Case Report - Annisa Fildza Hashfi; Winda Wijayanti; Nurrachmat Mulianto (HM Publisher, 2022)
Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae. This disease has a high transmission ability and can cause physical disability and have an impact on the social life of the sufferer because of the negative stigma about leprosy. This study aims to describe the examinations performed in the diagnosis and treatment of patients with multibacillary leprosy, borderline lepromatous type. Case presentation: A 43-year-old woman with a chief complaint of redness on the arm since 1 year ago. The patches are not itchy, painless, stiff, and numb. Since 3 months ago, the patient complained of red patches increasing and spreading to the trunk and legs. Dermatological examination found in the facial region et truncus anterior et posterior et superior, and inferior extremities bilateral showing multiple erythematous plaques, well-demarcated with scales in several parts. Sensory function examination revealed a decrease in lesions on the face, superior and inferior extremities, and anterior and posterior trunks. Negative AFB examination and biopsy results support the diagnosis of borderline lepromatous type (BL) multibacillary leprosy (MB). Conclusion: Clinical findings in the form of hypopigmented lesions that feel numb is a cardinal signs of leprosy. Asymmetrical distribution of lesions with a number of more than 5 lesions accompanied by impaired nerve function in the form of decreased sensibility is a characteristic of MB leprosy. Histopathological features support the diagnosis of MB type BL leprosy even though the results of the skin slit smear examination were negative.